Comparing the objective motivational climate created by grassroots soccer coaches in England, Greece and France - Tessier, D.; Smith, N.; Tzioumakis, Y.; Quested, Eleanor; Sarrazin, P.; Papaioannou, A.; Digelidis, N.; Duda, J. (2013)
The coach-created motivational climate is a key determinant of athletes' welfare and degree of optimal functioning when taking part in sport. The purpose of this study, grounded in a self-determination theory and achievement goal theory-integrated framework, was to investigate to what extent the differences in the objective motivational climate created by the coaches involved in the European-wide "Promoting Adolescent Physical Activity" project were a function of their country affiliation (i.e. England, Greece and France). Fifty-seven coaches (55 men and 2 women) from England, Greece and France were selected to take part in the study. Each coach was videotaped during one complete training session using a digital camcorder and microphone. The recently developed Multidimensional Motivational Climate Observation System was used to code the coach-created motivational climate in terms of need-supportive and need-thwarting environmental dimensions. Results showed that (1) coaches were observed to emphasise on a more need-supportive environment than a need-thwarting one (i.e. 69.9% and 30.1% of the whole behaviours coded, respectively) and (2) although coaches' interpersonal styles varied significantly across countries, the general pattern of the coach-created environment observed in the three countries had a similar profile. © 2013 International Society of Sport Psychology.